KONSTITUSIONALITAS MODEL PENGISIAN JABATAN WAKIL KEPALA DAERAH DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH (PILKADA) - Wilda Prihatiningtyas (Universitas Airlangga, 2018)
The local government is very important in the context of unitary state according to Indonesia Constitution (UUD NRI 1945). There is no constitution in the world that does not regulate important thing regarding to local government or state government explicitly. Therefore formulations charging a place on local government may be related parameter early governance in the region. There are 2 (two) important issues relating to constitutionality of model charging office deputy head of the regions in the regional head election. First, standing of deputy head based on the laws. Second, constitutionality of model charging office deputy head of the regions based on Law No. 1/2015 jo Law No. 8/2015. In this paper, there are 2 (two) models in placing the position of deputy head of region. First, the position is hierarchical under the head of the region with the argument that the deputy head of the region appointed by the head of the region. And second, the position of the deputy head of the region is considered parallel to the regional head because both are directly elected by the people in a package.